A Review Analysis: Implementation of STEAM Project Based Learning in Natural Science Learning - Nurhasnah Nurhasnah; Festiyed Festiyed; Yerimadesi Yerimadesi (SEJ (Science Education Journal), 2023)
The development of technology 4.0 and social 5.0 has a considerable influence on educational change. Education in the 21st century requires students to have the competencies needed to face the challenges of the times. One of the efforts made is with a learning model that can develop these abilities, namely STEAM-PjBL. The purpose of this research is to analyze implementation trends of STEAM-PjBL in science learning from elementary school level to university level. This research is a literature study by collecting 19 articles. This study adopted the review process by Sharif (2019), by 1) formulating research questions; (2) setting the inclusion criteria (Table 1); (3) search for articles in various databases (Google Scholar, ERIC, DOAJ, journal websites) by typing the keywords “STEAM” “STEAM-PjBL, “STEAM-PjBL in science education” and “science education”; (4) article coding using Paper Classification Form (PCF); (5) identify patterns across articles; (6) synthesize these patterns to answer the research question. The results obtained The implementation of STEAM-PjBL research in science learning has a very good contribution in growing and improving the skills needed by students in facing the challenges of the 21st century. Learning in the current condition, which is still a COVID-19 pandemic, can be an option for schools and teachers to implement STEAM-PjBL so that they can realize the learning goals to be achieved.